PENGEMBANGAN KOMIK ANIMASI BERMUATAN CERITA RAKYAT SASAK UNTUK MENINGKATKAN KEMAMPUAN LITERASI MEMBACA DAN MENULIS SISWA KELAS IV SEKOLAH DASAR - Zain, Moh. Irawan; Tahir, Muhammad; Zain Amrullah, Lalu Wira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Folklore of sasak te godek-godek and te tuntel-tuntel is a story that has existed for generations but is only told by word of mouth and few records in the form of storybooks without pictures. So that its existence began to be rarely found. This encourages the need for the development of stories in the form of animated comics. The existence of animated comics as a medium for learning Indonesian is very important, especially to improve the literacy of reading and writing skills of grade IV elementary school students. In this regard, this study aims to design animated comics containing sasak folklore to improve the reading and writing literacy skills of grade IV elementary school students. The method that will be used in achieving the objectives of this research is design research developed by Plomp. This development model has 3 phases, namely the initial research stage, the development stage, and the assessment stage. The initial research stage consists of problem identification and needs analysis activities, reviewing literature, and developing an initial framework for product development. Then in the development stage consists of activities to develop a product prototype for testing while conducting a formative evaluation of the product. Finally, in the assessment stage, namely conducting a summative evaluation of the product being developed. The results of this study obtained a product value of 90% feasibility from media experts and 81% material experts, at the stage involving respondents from teachers and students, a feasibility of 98% was produced.